URGENSI TRI PUSAT PENDIDIKAN DALAM PERSPEKTIF ISLAM - Seno Seno (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Tricenter of education is an educational theory put forward by Ki Hajar Dewantoro, the founder of Taman Siswa, who is recognized as the Father of National Education. The education center referred to here is that the educational environment includes education in the family environment, education in the school environment, and education in the community in an Islamic perspective. These three environments greatly affect the growth and development of children. This research is library research because the object of the study is literature in the form of the concept of Tri Center of Education. Therefore, the data needed are textual data, namely texts about the Three Education Centers in books, journals and others with interpretations of the Koran, hadith and opinions of scholars. The approach methods in this research are the description method, content analysis method and hermeneutic method. The data and facts show that the generation of the companions of the Prophet sallallaahu Alaihi Wasallam is the best generation in the history of mankind, because they live in an Islamic family education environment, an Islamic school education environment, and an Islamic community environment as well. namely living with the Prophet sallallaahu 'alaihi wasallam who became a real model for their lives. Some programs for students to be tough and have the resilience to face the slander of the world and religion in the digital era are living with the Koran and sticking to it, the need for value education or immune education for students, the need to present examples to students. Tripusat pendidikan adalah teori pendidikan yang dikemukakan oleh Ki Hajar Dewantoro pendiri taman siswa yang diakui sebagai Bapak Pendidikan Nasional. Tripusat pendidikan yang dimaksud disini adalah lingkungan pendidikan itu meliputi pendidikan di lingkungan keluarga, pendidikan di lingkungan sekolah, dan pendidikan di lingkungan masyarakat dalam perspektif Islam tiga lingkungan ini sangat mempengaruhi masa pertumbuhan dan pengembangan anak. Penelitian ini adalah penelitian pustaka karena yang dijadikan objek kajian adalah karya literatur berupa konsep Tri Pusat Pendidikan. Oleh karena itu, data-data yang diperlukan ialah datadata tekstual, yaitu teks-teks tentang Tri Pusat Pendidikan yang ada dalam kitab buku-buku, jurnal dan lainnya dengan interpretasi al-Quran, hadis dan pendapat ulama ulama. Adapun metode pendekatan pada penelitian ini adalah Metode Diskripsi, Metode Analisis Isi dan Metode Hermeneutik. Data dan fakta menunjukkan bahwa generasi sahabat Rasulullah Shallallahu Alaihi Wasallam adalah generasi terbaik dalam perjalanan hidup sejarah umat manusia, karena mereka hidup dalam lingkungan pendidikan keluarga yang Islami, lingkungan pendidikan sekolah yang Islami, dan lingkungan masyarakat yang Islami pula. yaitu hidup bersama Rasulullah Shallallahu alaihi wasallam yang menjadi model sesungguhnya bagi kehidupan mereka. Beberapa program bagi peserta didik agar tangguh dan memiliki daya kenyal menghadapi fitnah dunia dan agama di era digital adalah hidup bersama Alquran dan berpegang teguh kepadanya, perlunya pendidikan nilai atau pendidikan imun bagi peserta didik, perlunya menghadirkan keteladanan kepada peserta didik..